To simplify the expression 3.5 times 3.7 using the product rule of exponents, we need to add the exponents since the bases are the same.
The expression can be rewritten as:
3.5 × 3.7 = (3 × 10^0 + 0.5) × (3 × 10^0 + 0.7)
Using the product rule of exponents, we can get:
= (3 × 10^0) × (3 × 10^0) + (3 × 10^0) × 0.7 + (3 × 10^0) × 0.5 + 0.7 × 0.5
= 3^2 × 10^(0 + 0) + 3 × 10^0 × 0.7 + 3 × 10^0 × 0.5 + 0.35
= 9 × 10^0 + 2.1 × 10^0 + 1.5 × 10^0 + 0.35
= 9 + 2.1 + 1.5 + 0.35
= 13.95
Therefore, 3.5 times 3.7 is equal to 13.95.
Use the product rule of exponents to simply 3,5times 3,7
1 answer